An analysis of the continuing professional activities for pharmacists in the continuing professional development accreditation in the Philippines - Babanto, Leonides II O.; Fabros, Ace Marion A.; Remonte, Jaime Antonio Y.; Guttierrez, Margarita M. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2025)
Pharmacists are essential healthcare professionals whose roles continue to expand, requiring ongoing competency through Continuing Professional Development (CPD). In the Philippines, CPD is mandated by law as a requirement for license renewal. While CPD enhances skills and career growth, barriers such as cost and accessibility persist. Despite its importance, there is limited research on the current CPD landscape for Filipino pharmacists.

The present study collected data from the CPD Accreditation System in the Philippines for pharmacists offered in 2022-2024. The CPD activities were characterized using descriptive statistics and the association between their characteristics and CPD units awarded were analyzed using multiple linear regression.

This study analyzed 1,469 accredited CPD activities for Filipino pharmacists, finding most were free, online, and focused on professional practice enhancement. Activities averaged 5.02 CPD units and 9.57 hours, with Firms and Online learning as the most common providers and modalities. Cost analysis revealed substantial variation: government and online activities were the most affordable per unit and hour, while conventions, study tours, and activities by firms or in NCR were the most expensive. Units earned per hour were generally consistent across subgroups, however, cost differences were observed among providers, modalities, and regions.

Regression analysis showed that longer duration, certain modalities, specific topics, and some regions were associated with higher CPD units, while in-house and open-to-all activities were associated with fewer units.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, July 2025
Keywords: Pharmacists -- Continuing education -- Accreditation -- Philippines; Continuing professional development -- Policies and guidelines -- Philippines